Love and Liberation : Humanitarian Work in Ethiopia's Somali Region - Carruth, Lauren, 1980- (Book collections on Project MUSE., 2021)
"An ethnography of the global humanitarian industry, centered on the appropriation and reimagining of relief by Somalis in Ethiopia. Policymakers and aid workers there are creatively using humanitarian funding to build autonomous governmental structures. In so doing, Somalis are essentially decolonizing Ethiopia and localizing the aid industry"--